Transient thermal elastohydrodynamic simulation of a DLC coated helical gear pair considering limiting shear stress behavior of the lubricant. (May 2016) - Beilicke, Ronny; Bobach, Lars; Bartel, Dirk
Abstract: A transient three-dimensional thermal elastohydrodynamic calculation model is introduced to simulate the contact of tooth flanks of helical gear pairs with involute gearing. At any time, contact geometry is derived from the real involute curves of gears. In addition to the consideration of mass conserving cavitation and the non-Newtonian fluid behavior, models to capture conditions of mixed friction and microhydrodynamic effects are included. To consider the non-Newtonian fluid behavior, a shear thinning fluid model with limiting shear stress is applied. A selected helical gear pair is used as example to examine the influence DLC coated tooth flanks have on tribological behavior. It shows that friction and temperature behavior of the gearing can be significantly influenced with DLC coating. Highlights: Transient TEHL calculation model to simulate helical gear pairs. Non-Newtonian fluid behavior with limiting shear stress. Consideration of states of mixed friction and microhydrodynamics. Application of multi-layered coatings on the tooth flanks. Calculations to show the influence of DLC coatings on the tribological behavior.